ANALISIS FILOGENETIKA TANAMAN TIMUN APEL BERBASIS METODE RAPD MENGGUNAKAN PRIMER OPA 12 DAN OPA 18 - Nur Meida Tri Rezeki, Meida (2020)
Apple cucumber is one of the holticulture commodity in Karawang, Aceh and Jember. Based on the previous research, Apple cucumber plant is the result from natural hybridization between Cucumber and Melon. The form of Apple cucumber fruit like an Apple but the texture and the taste just like Melon. Although scientific information of Apple cucumber plant is still very limited as specially about the taxonomy of Apple cucumber plant. Therefore this study aims to analysis phylogenetic relationship Apple cucumber plant with other species wich belonging to family Cucurbitaceae. Analysis phylogenetic relationship based on RAPD markers using OPA 12 and OPA 18 primers. The data of RAPD is being combine with DNA sequence derived of Internal Transribed Spacer (ITS) was obtained from GeneBank NCBI. In this study, the reconstruct of phylogenetic tree is using PAUP 4.0 with maximum parsimony methode. Phylogenetic analysis based on RAPD data showed that Apple cucumber is more related to Melon rather than other species wich belonging to family Cucurbitaceae, meanwhile based on combine data RAPD and ITS both are support the result of previous research that Apple cucumber is hybridization result between Melon and Cucumber with high boostrap value (100%). Overall, primer OPA 12 and primer OPA 18 succeed to analysis phylogenetic relationship Apple cucumber with other species wich belonging to family Cucurbitaceae. The result of this study, can be used as based knowlaged in the prepararation of an Apple cucumber plant taxonomy.